1992
DOI: 10.1177/0951692892004003002
|View full text |Cite
|
Sign up to set email alerts
|

Success on the Commons

Abstract: The notorious `tragedy of the commons' is incorrectly held to be the eventual fate of all resources that are used collectively rather than by individual private owners. This essay reviews several examples around the world of successful collective management of environmental resources - institutional regimes that have operated for decades or even centuries without resulting in degradation of resources. It then explores the features shared by these historically unconnected institutional regimes in order to begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…The best practices model (Figure 1) recommends formal intercoder reliability testing on a subset of the dataset, as well as iterative intercoder agreement testing throughout and after the formal coding process (MacQueen et al 1998;Mayring 2000;Hruschka et al 2004;Guest and MacQueen 2008). We have found that this step is often missing from reports on studies of CPRs using meta-analyses (Netting 1976;Wade 1984;Berkes 1989;Ostrom 1990;McKean 1992;Baland and Platteau 1999;Bardhan and Mookherjee 2006;Cox 2014;Epstein et al 2014;Fleischman et al 2014;Villamayor-Tomas et al 2014). Hruschka et al (2004) explain that a reluctance to assess coder agreement is common in some branches of social science because: (1) researchers may generally believe that the quantification of qualitative data is unnecessary because qualitative research is a "distinct paradigm" that cannot or should not be subject to a quantitative evaluation; and…”
Section: Perform Intercoder Reliability Testing and Iteratively Refinementioning
confidence: 99%
See 1 more Smart Citation
“…The best practices model (Figure 1) recommends formal intercoder reliability testing on a subset of the dataset, as well as iterative intercoder agreement testing throughout and after the formal coding process (MacQueen et al 1998;Mayring 2000;Hruschka et al 2004;Guest and MacQueen 2008). We have found that this step is often missing from reports on studies of CPRs using meta-analyses (Netting 1976;Wade 1984;Berkes 1989;Ostrom 1990;McKean 1992;Baland and Platteau 1999;Bardhan and Mookherjee 2006;Cox 2014;Epstein et al 2014;Fleischman et al 2014;Villamayor-Tomas et al 2014). Hruschka et al (2004) explain that a reluctance to assess coder agreement is common in some branches of social science because: (1) researchers may generally believe that the quantification of qualitative data is unnecessary because qualitative research is a "distinct paradigm" that cannot or should not be subject to a quantitative evaluation; and…”
Section: Perform Intercoder Reliability Testing and Iteratively Refinementioning
confidence: 99%
“…Long-term efforts to understand social-ecological systems (SES) involving the management of common pool resources (CPR 1 ) has led to the generation of a large body of data composed primarily of case studies (Wade 1984;Berkes 1989;Ostrom 1990;McKean 1992;Baland and Platteau 1999; Bardhan and Mookherjee 2006;Cox 2014;Epstein et al 2014). If we are to understand CPR governance, we must be able to make comparisons across case studies but are challenged to develop reliable methods of making this often complex and messy data comparable.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of utilization of common forests by commoners has changed drastically from the past. Historically, hamlet residents used common forests to gather wood for fuel, to make charcoal, and to use materials as fodder, fertilizer, and building or tool materials mainly for household consumption (McKean, 1992). In the early modern era of Japan, the Edo period (1603-1867), each hamlet or groups of hamlets used certain tracts of forests under a regime of customary rights before land ownership had been established, since the modern concept of sole land ownership was not recognized at that time.…”
Section: Use Of Common Forests In Japanmentioning
confidence: 99%
“…Uma importante discussão que se insere na Abordagem dos Comuns é aquela acerca dos regimes sob os quais esses recursos podem ser geridos com intuito de garantir seu uso de forma sustentável (Hardin, 1968;Berkes et al, 1989;Dietz et al, 2002;McKean, 1992;Ostrom, 2000;Fenny et al, 2001;Vieira et al, 2005;Kalikoski, 2007;Berkes, 2009;Medeiros, 2009). Essa abordagem tem permitido aos pesquisadores compreenderem os fatores que influenciam as condições e os problemas em torno do uso sustentável do pool dos recursos naturais de uso comum.…”
Section: Introductionunclassified
“…Diversos estudos (McKean, 1992;McKean, 2000;Vieira et al, 2005;Kalikoski, 2007;Berkes, 2009;Medeiros, 2009;Berkes, 2010) defendem que a formulação e a implantação de instituições formais, para a gestão destes recursos, devem reconhecer e incorporar os conhecimentos e as práticas dos usuários e das instituições informais por eles subsidiadas. Caso contrário, essas instituições podem entrar em colapso, gerando a degradação dos recursos naturais e a desestruturação de sistemas socioprodutivos implicados.…”
Section: Introductionunclassified